Olfactory deficits predict cognitive decline and Alzheimer dementia in an urban community - Devanand, D.P. (Neurology, 2015)
OBJECTIVE: To determine the predictive utility of baseline odor identification deficits for future cognitive decline and the diagnosis of Alzheimer disease (AD) dementia. METHODS: In a multiethnic community cohort in North Manhattan, NY, 1,037 participants without dementia were evaluated with the 40-item University of Pennsylvania Smell Identification Test (UPSIT). In 757 participants, follow-up occurred at 2 years and 4 years. RESULTS: In logistic regression analyses, lower baseline UPSIT scores were associated with cognitive decline (relative risk 1.067 per point interval; 95% confidence interval [CI] 1.040, 1.095; p < 0.0001), and remained significant (relative risk 1.065 per point interval; 95% CI 1.034, 1.095; p < 0.0001) after including covariates. UPSIT, but not Selective Reminding Test–total immediate recall, predicted cognitive decline in participants without baseline cognitive impairment. During follow-up, 101 participants transitioned to AD dementia. In discrete time survival analyses, lower baseline UPSIT scores were associated with transition to AD dementia (hazard ratio 1.099 per point interval; 95% CI 1.067, 1.131; p < 0.0001), and remained highly significant (hazard ratio 1.072 per point interval; 95% CI 1.036, 1.109; p < 0.0001) after including demographic, cognitive, and functional covariates. CONCLUSIONS: Impairment in odor identification was superior to deficits in verbal episodic memory in predicting cognitive decline in cognitively intact participants. The findings support the cross-cultural use of a relatively inexpensive odor identification test as an early biomarker of cognitive decline and AD dementia. Such testing may have the potential to select/stratify patients in treatment trials of cognitively impaired patients or prevention trials in cognitively intact individuals.